(In)justiça tributária em Aracaju : estudo sobre os aspectos distributivos do IPTU à luz da constituição - Nogueira, Maurício Soares de Sousa (2018)
The present study aims to provide the elements for a conception of municipal tax justice focused on maximizing the social function of the city and on the spatial perspectives of the excluded. The Urban Land and Territorial Tax (in portuguese, IPTU) has an important distributive aspect, precisely because it is a direct tax, difficult to avoid, and wich legally admits the progressivity of the rates. The theoretical framework that guides the analysis throughout the work used the following concepts: the idea of tax justice of Ricardo Lobo Torres; the concept of the right to the city, developed by Lefebvre; John Rawls's conception of justice as fairness; and the idea of progressivity, from Thomas Piketty's perspective. Regarding the methodology, different perspectives were adopted, based on historical, dogmatic, political-tributary and comparative law aspects. Among the results of this research it is highlighted the dubious behavior of the IPTU., considering that from the payers' point of view, its structure is regressive, with the poorest taxpayers suffering a greater taxation. The main cause is the regressivity in official real estate evaluations in relation to market values. The relevance of the present study lies in the fact that improving the progressiveness of the tax system can contribute to overcoming the high income inequality in Brazil.